2007
DOI: 10.1242/jcs.000331
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the transcription factor NFAT2 in human neutrophils: IgE-dependent, Ca2+- and calcineurin-mediated NFAT2 activation

Abstract: NFAT (nuclear factors of activated T cells) proteins constitute a family of transcription factors involved in mediating signal transduction. The presence of NFAT isoforms has been described in all cell types of the immune system, with the exception of neutrophils. In the present work we report for the first time the expression in human neutrophils of NFAT2 mRNA and protein. We also report that specific antigens were able to promote NFAT2 protein translocation to the nucleus, an effect that was mimicked by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 45 publications
(71 reference statements)
4
29
1
Order By: Relevance
“…In this context active calcineurin has previously been detected in human neutrophils [36], [39], [55], as well as other members of the signalling cascade such as NFAT2 (nuclear factor of activated T cells 2) [37]. In addition a number of previous studies have indicated calcineurin inhibition significantly influenced neutrophil activity, inhibiting chemokinesis, adhesion and motility on vitronectin, response to angiotensin II, as well as a reduction in phagocytic activity [38][41], [43], [44].…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In this context active calcineurin has previously been detected in human neutrophils [36], [39], [55], as well as other members of the signalling cascade such as NFAT2 (nuclear factor of activated T cells 2) [37]. In addition a number of previous studies have indicated calcineurin inhibition significantly influenced neutrophil activity, inhibiting chemokinesis, adhesion and motility on vitronectin, response to angiotensin II, as well as a reduction in phagocytic activity [38][41], [43], [44].…”
Section: Resultsmentioning
confidence: 91%
“…This investigation was prompted by a number of reports indicating that human neutrophils possess a functional calcineurin system [36], [39], [55], including nuclear signalling components such as NFAT2 [37], and that its pharmacological modulation influences neutrophil behaviour [38][41], [43], [44].…”
Section: Discussionmentioning
confidence: 99%
“…77 NFAT signaling has now been demonstrated in several different types of granulocytes (Table 1). NFAT expression was first described as an important inducer of inflammatory responses in human neutrophils, 82 which express both NFAT2 and NFAT4. IgE-mediated neutrophil expression of cyclo-oxygenase and release of prostaglandins are regulated by NFAT translocation.…”
Section: Role Of the Nfat Pathway In Innate Immunity 1383mentioning
confidence: 99%
“…IgE-mediated neutrophil expression of cyclo-oxygenase and release of prostaglandins are regulated by NFAT translocation. 82 Expression of IL-10, Cox2, Egr1, and Egr2 genes is impaired in mice that conditionally lack calcineurin subunit B in neutrophils. Each of these genes is dependent on calcineurin/NFAT signaling and exerts an important role in innate immune responses.…”
Section: Role Of the Nfat Pathway In Innate Immunity 1383mentioning
confidence: 99%
“…Quantitative real-time RT-PCR (qPCR) was performed using the SYBR Premix Ex Taq (Perfect Real Time) Premix (TaKaRa Bio, Otsu, Japan) or the LightCycler FastStart DNA Master SYBR Green I kit (Roche, Mannheim, Germany) in a fluorescent temperature cycler (LightCycler; Roche). Primer sequences were obtained from previous publications (6,15,35,38) (Table 1). The qPCR protocol included initial denaturation at 95°C for 10 min (LightCycler FastStart) or 10 s (SYBR Premix), followed by 40 -50 PCR cycles of 95°C for 5 s and 60°C for 20 s (SYBR Premix), or 95°C for 10 s, 60°C for 10 s, and 72°C for 12 s (LightCycler FastStart).…”
Section: Methodsmentioning
confidence: 99%